Effect of eccentric training on knee strength and hamstring flexibility in active females with hamstring tightness: A clinical trial study - Aisan Fard Mehregan (مجله دانشگاه علوم پزشکی گرگان, 2021)
Background and Objective: Strength and flexibility are the factors affecting the athletechr('39')s performance. This study was done to determine the effect of eccentric training on knee strength and hamstring flexibility in active females with hamstring tightness. Methods: In this clinical trial study, 24 active female athletes with hamstring tight were randomly divided into intervention and control groups. For measurement of strength, including the eccentric and concentric peak torque and the time to reach the peak torque in speeds of 60 and 180 degrees per second, isokinetic dynamometer device .For measurement of hamstring flexibility, a passive knee extension test was used six weeks before and after the eccentric training of hamstring. Results: After six weeks of eccentric training, a significant  improvement was observed in test scores of passive knee extension (PKE) test and also in the maximum torque and time to reach the maximum torque eccentric flexor knee in angular velocity of 60 degrees per second in the interventional  group compared to controls (P<0.05). Conclusion: Eccentric training increases flexibility and eccentric strength of hamstring muscles in active females with hamstring tightness.